Institutional trading, information production, and the choice between spin-offs, carve-outs, and tracking stock issues - Chemmanur, Thomas J.; Liu, Mark H. (Journal of Corporate Finance, 2011)
We analyze a firm's choice between spin-offs, equity carve-outs, and tracking stock issues and the role of institutional investors in corporate restructuring. We model a firm with two divisions. Insiders have private information about firm value and face an equity market with retail and institutional investors. We show that restructuring increases information production by institutional investors (relative to that about the consolidated firm): the highest increase in information production arises from spin-offs, the next highest from carve-outs, and the lowest from tracking stock issues. Insiders with the most favorable private information implement spin-offs; those with less favorable private information implement carve-outs; those with even less favorable private information implement tracking stock issues; and those with unfavorable private information remain consolidated. We explain the positive announcement effect and increase in analyst coverage associated with all three forms of restructuring. Our model also generates a number of novel testable predictions for firms' choice between spin-offs, carve-outs, and tracking stock issues, and for institutional trading around these three forms of restructuring.